Efeito da vagotomia associado ou não à esplenectomia sobre a histologia do fígado em ratos obesos-msg - Amaral, Ana Claudia (2019)
The objective of this study was to evaluate the effect of subdiaphragmatic vagotomy associated or not to splenectomy on the liver morphology in obese rats induced by glutamate monosodium (MSG). Newborn male rats received during the first five days of life injections of either 4 g MSG/body weight kg (MSG group) or 1.25 g saline/body weight kg - control group (CTL). At 60 days of age the MSG obese animals were subjected to subdiaphragmatic vagotomy (MSG VAG), or splenectomy (MSG ESP) or vagotomy associated with splenectomy (MSG VAG ESP), or false operation (MSG FO). At 150 days the animals were euthanized. The perigonadal and retroperitoneal fat stocks were higher in MSG FO animals compared to CTL. Retroperitoneal fat weight was lower in MSG VAG, MSG ESP and MSG VAG ESP compared to MSG FO groups. The degree of hepatic steatosis was lower in MSG VAG animals when compared to MSG FO. Thus the vagotomy had a protective effect on the installation of the nonalcoholic fatty liver disease (NAFLD) in obese animals MSG. However, splenectomy exacerbated this parameter in animals from the MSG ESP group compared to the MSG FO group. Interestingly the degree of steatosis was similar between the MSG VAG ESP animals and the MSG FO group. Thus, it is concluded that the vagus nerve and the spleen play an important but independent role in the installation of NAFLD in the MSG-induced obesity model.